2012
DOI: 10.1159/000351734
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cervical Intraosseous Schwannoma

Abstract: Intraosseous schwannoma of the spine is an extremely rare tumor, with only 18 cases reported so far in the literature. We describe the 1st case of intraosseous schwannoma in the pediatric age group, which was treated successfully, and we review the pertinent literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Yeh et al have published an 11‐year‐old boy with schwannoma of the C 6‐7 that was presented with forearm pain and progressive weakness and clawing hand 11 . Mohanty et al reported another schwannoma of the neck in a 10‐year‐old boy, presented also with swelling in the neck and symptoms from swallowing and voice hoarseness that was arising from C 4 body and with destruction of the vertebral body 12 . Landi et al described the case of a 8‐year‐old female affected by a progressive paraparesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeh et al have published an 11‐year‐old boy with schwannoma of the C 6‐7 that was presented with forearm pain and progressive weakness and clawing hand 11 . Mohanty et al reported another schwannoma of the neck in a 10‐year‐old boy, presented also with swelling in the neck and symptoms from swallowing and voice hoarseness that was arising from C 4 body and with destruction of the vertebral body 12 . Landi et al described the case of a 8‐year‐old female affected by a progressive paraparesis.…”
Section: Discussionmentioning
confidence: 99%
“…11 Mohanty et al reported another schwannoma of the neck in a 10-year-old boy, presented also with swelling in the neck and symptoms from swallowing and voice hoarseness that was arising from C 4 body and with destruction of the vertebral body. 12 Landi et al described the case of a 8-year-old female affected by a progressive paraparesis. She had a schwannoma at the level of T10-T11.…”
Section: Discussionmentioning
confidence: 99%